Advanced Multimedia and Ubiquitous Engineering Future Information Technology Volume 2 - Park, James J. (Jong Hyuk).; Chao, Han-Chieh.; Arabnia, Hamid; Yen, Neil Y.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
This volume brings together contributions representing the state-of-the-art in new multimedia and future technology information research, currently a major topic in computer science and electronic engineering. Researchers aim to interoperate multimedia frameworks, transforming the way people work and interact with multimedia data. This book covers future information technology topics including digital and multimedia convergence, ubiquitous and pervasive computing, intelligent computing and applications, embedded systems, mobile and wireless communications, bio-inspired computing, grid and cloud computing, semantic web, human-centric computing and social networks, adaptive and context-aware computing, security and trust computing and related areas. Representing the combined proceedings of the 9th International Conference on Multimedia and Ubiquitous Engineering (MUE-15) and the 10th International Conference on Future Information Technology (FutureTech 2015), this book aimsto provide a complete coverage of the areas outlined and to bring together researchers from academic and industry and other practitioners to share their research ideas, challenges, and solutions. .
From the Contents: The study on the detection of the damaged file using the graph of the information entropy for Security Management -- Enhancing Dataset Processing in Hadoop YARN Performance for Big Data Applications -- A Multimetric Approach for Discriminating Distributed Denial of Service Attacks from Flash Crowds -- A Supporting Tool for Spiral Model of Cryptographic Protocol Design with Reasoning-based Formal Analysis.
Keywords: Telecommunication; Computer networks .; Multimedia systems; Communications Engineering, Networks; Computer Communication Networks; Multimedia Information Systems